Navigating Delays: A Comprehensive Study of Public Building Retrofitting Projects in Kathmandu Valley - Bhattarai, Subash Kumar; Rayamajhi, Laxman; Lamichhane, Sanju; Arayal, Sushma (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.004 The objective of the study was to find out the present scenario of delays of retrofitting of public building with case of 11projects of Kathmandu valley. An observation and study of the project document is carried out along with questionnaire survey with 50 respondents. The maximum rate of delay in the retrofitting project is found to be 167% time overrun and minimum is found to be 42% of time overrun. Only one project among them is within the schedule with physical progress of 22%. A multiple linear regression analysis was performed to examine the influence of the variables Time overrun (Months) and Time extension with respect to initial contract (%) on the variable Physical Progress. A model summary model is obtained as follows: Physical Progress = 0.57 + 0.02 * Time overrun (Months) - 0.15 * Time extension with respect to initial contract (%) The top ranked specific delay contributing factors in a retrofitting project are as found as Impractical project schedule and duration (frequent changes in critical path), Unavailability of the numbers and skilled workforce for retrofitting projects, Delays occurred due to lack of coherence in architectural, structural, electrical, sanitary, and HVAC drawings, Approvals of shop drawings submitted by the contractor and Unavailability of the specific materials as per BOQ.